Changes in organoleptic and biochemical parameters of three commercially important marine fish species of Bay of Bengal during ice storage - Hossain, Md Ismail; Shikha, Fatema Hoque; Ghosh, Riton (Fundamental and Applied Agriculture, 2019)
The study was conducted to observe the changes in organoleptic and bio- chemical parameters of three marine fish species of Bay of Bengal during ice storage. The fish species, viz., Bombay duck (Harpadon nehereus), silver jewfish (Johnius argentatus) and ribbon fish (Trichiurus haumela) were col- lected from the landing center of Cox’s Bazar and frozen transported to Mymensingh city. After arrival in Mymensingh, the fish samples were stored in ice for about 9 days by applying fresh flakes of ice to the fishes at regular interval. During the storage period, required amount of fish samples were taken out from the ice box at two-day interval to collect data on changes in organoleptic and biochemical parameters (e.g., analysis of proximate composition, TVB-N and pH). During ice storage, the overall organoleptic qualities of all fish samples were in acceptable condition up to 9 days. The fish samples stored in ice exhibited excellent quality on the basis of physical characteristics until 3rd day of storage. Biochemical analyses revealed that the percent mois- ture content of Bombay duck, silver jewfish and ribbon fish increased with the lapse of storage period whereas the percent protein content decreased With the progress in storage period. Lipid content also decreased gradually in the same samples but the percent ash content of the samples changed very little. The values for total volatile base nitrogen (TVB-N) of the three fish samples increased slightly during the storage period. The pH value of the fish samples also increased throughout the storage. So, the present study conclude that the organoleptic characteristics and biochemical parameters of above mentioned fish changes during ice storage of 9 days but found acceptable for human consumption.